Characterization of peat soil hydraulic conductivity and its dependence on vegetation type in mountain wetlands - Crockett, Audrey, author; Ronayne, Michael, advisor; Cooper, David, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2015)
Peat-forming wetlands enhance biodiversity and provide carbon storage in mountain environments. Persistence of these wetlands requires sustained water inflows. Reduced or altered inflows associated with climate change could lower the water table, potentially resulting in peat oxidation and carbon release to the atmosphere, as well as the loss of wetland plant and animal species. An understanding of the hydrology and site hydraulic properties is necessary to manage mountain wetlands and assess their vulnerability to climate change. This study characterized the hydraulic conductivity of wetland peat soils in Rocky Mountain National Park (RMNP). Peat-forming wetlands in RMNP are classified as fens because their main source of water is groundwater. Fens in RMNP contain a broad range of vegetation. Dominant vegetation type is one factor that may influence peat hydraulic conductivity, so the fens in this study were divided based on dominant vegetation type. The three vegetation classifications used were “large sedge,” “small sedge,” and “heterogeneous,” indicating that the fens were dominated by large sedges (mainly Carex); small sedges (Eleocharis quinqueflora); or a mixture of woody plants, sedges, and moss; respectively. In this study, field measurements were combined with a numerical model and parameter estimation scheme to produce estimates of hydraulic conductivity with a high degree of confidence. Single-ring infiltration tests were performed in the field. A numerical model was constructed, and a parameter estimation scheme was used to find the hydraulic conductivity that best reproduced the results of the single-ring infiltration test. The fens dominated by small sedges have significantly lower hydraulic conductivity than the fens dominated by large sedges or heterogeneous vegetation. Fens which have relatively high hydraulic conductivity (those dominated by large sedges or a heterogeneous mixture of plants) may be especially at risk of draining under changing climate regimes. Small-sedge fens may be more likely to maintain a high water table due to their low hydraulic conductivity.